Enhanced desorption from solid deuterium driven by charging with keVelectrons - Schou, Jørgen; Thestrup, Birgitte (Recent Contributions to Physics, 2015)
Films of solid deuterium at a temperature around 3 K have been irradiated by 1.5 or 2 keV electrons. The films were deposited on the silver electrode of a quartz crystal microbalance (QCM) suspended below a pumped liquid helium cryostat [1,2]. The thickness of the films ranged from 10 nm to up to 5 m. The initial film thickness and the mass loss as result of desorption were monitored by the QCM. The electron beam current was kept at about or below 100 nA to avoid beam-induced evaporation.